ANALISIS KANDUNGAN NUTRISI DAGING DAN TEPUNG TERIPANG PASIR (Holothuria scabra J.) SEGAR - Rahman Karnila; Made Astawan; Sukarno Sukarno; Tutik Wresdiyati (Berkala Perikanan Terubuk, 2011)
Sea cucumber (Holothuria scabra J.) is one of fishery commodities whichcontain high nutritional and economic value. This study aims were 1) thephysical characteristics of sea cucumber, 2) nutrient content (proximate) seacucumbers fresh meat, and 3) the yield and nutrient content (proximate) seacucumber powdery fresh meat. The study was conducted in four stages of theexperiment: 1) Preparation of meat of sea cucumber, 2) analysis of nutrientcontent (proximate) sea cucumber fresh meat, 3) The making of powder of seacucumber meat , and 4) analysis of yield and nutrient content (proximate) seacucumber meat powder. Results showed the proportion between the parts of thebody meat: offal and gonads: the skin: water and dirt were 4:3:2:1 (w / w). Freshsea cucumber meat has a high nutrient content that is 87.03% water, 9.94%protein, 0.54% fat, 1.86% ash, and 0.64%. carbohydrate. The average yieldproduced approximately 10.16%. While the nutrient content (proximate) powderysea cucumber meat that is 9.13% water, 61.31% protein, 3.68% fat, 12.52% ash,and 13.36% carbohydrate.